Interaction Studies between Newly Synthesized Photosensitive Polymer and Ionic Liquids - In Tae Kim; Gi-Chung Kwon; Eun Ha Choi; Seung-Hyun Lee; Young Sun Kim; Jong Hyun Kim; Ju Hyon Cha; Sung Ho Kim; Pankaj Attri (International Journal of Polymer Science)
In this information age, different kinds of photosensitive materials have been used in the manufacture of information storage devices. But these photosensitive materials have the bane of low diffraction efficiency. In order to solve this problem, we have synthesized a novel photosensitive polymer from epoxy-based azopolymers (with three types of azochromophores). Furthermore, we have studied the interaction between this newly synthesized azopolymer and ionic liquids (ILs). For this purpose, we have used the ammonium and imidazolium families of ILs, such as diethylammonium dihydrogen phosphate (DEAP), tributylammonium methyl sulfate (TBMS), triethylammonium 4-aminotoluene-3-sulfonic acid (TASA), and 1-methylimidazolium chloride ([Mim]Cl). To investigate the molecular interaction between azopolymer and ILs, we have used the following spectroscopic methods of analysis: UV-visible spectroscopy, photoluminescence (PL) spectroscopy, Fourier transformed infrared spectroscopy (FT-IR), and confocal Raman spectroscopy. In this study, we have developed new photosensitive materials by combining polymer with ILs.